Definition of socialism - Gangopadhyay H P (Sreerampur Saptarshi Prakashan, 2004)
In this book the author has tried to do the seemingly- impossible job, relying mostly upon Marxian insights and Hegelian method. In that he had, of course, to shovel his way through piles of sticky, propaganda garbage.
Keywords: Socislism